1986
DOI: 10.1159/000234144
|View full text |Cite
|
Sign up to set email alerts
|

Contact-Sensitizing and Tolerogenic Properties of 2,4-Dinitrothiocyanobenzene

Abstract: Epicutaneous application of 2,4-dinitrothiocyanobenzene (DNTB) is said to result in specific immunological hyporesponsiveness and fails to induce contact sensitization. However, we demonstrate that topical exposure to DNTB causes activation of the draining lymph node in mice and the induction of contact sensitization in both rodents and a single human volunteer. In mice and rats, pre-exposure to DNTB failed to impair subsequent responsiveness to the cross-reactive allergen 2,4-dinitrochlorobenzene. These data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 9 publications
1
12
1
Order By: Relevance
“…Finally, our results may shed some light on the controversy regarding the sensitizing potential of DNTB. Indeed, unlike several reports, including the present work, some authors did not observe tolerance to DNTB but a weaker sensitization, concomitant with dendritic cell accumulation in regional lymph nodes (17,18). We propose that the frontier between tolerance and sensitization is narrow and easily crossed.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Finally, our results may shed some light on the controversy regarding the sensitizing potential of DNTB. Indeed, unlike several reports, including the present work, some authors did not observe tolerance to DNTB but a weaker sensitization, concomitant with dendritic cell accumulation in regional lymph nodes (17,18). We propose that the frontier between tolerance and sensitization is narrow and easily crossed.…”
Section: Discussioncontrasting
confidence: 94%
“…Our data are consistent with previously published observations and tend to confirm that DNFB and DNTB provide epitopes that can be recognized by the same T cells, yet differ in their capacity to prime the adaptive immunity (11,12,16). Although the value of DNTB as a tolerogen is still debated (17,18), this suggests that the level of inflammasome signaling induced by a given molecule may better predict its sensitizing potential than the antigenic properties itself.…”
Section: Dnfb and Dntb Provide Similar Epitopes Yet Differ In Their Cmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in experimental animals, topically applied 2,4-dinitrothiocyanobenzene (DNTB) has been reported by some authors to be capable of inducing immunological tolerance to itself and to cross-reactive dinitrophenyl compounds (3)(4)(5)(6). However, other authors could not demonstrate induction of tolerance by DNTB, but instead found it induced contact sensitivity in mice, rats, and a single human volunteer (7)(8)(9). It has been postulated that DNCB and DNTB form similar haptenated compounds in vivo; thus, the questions that arise based on the previous research are whether DNCB and DNTB provoke different cutaneous immune responses, and what forms the basis of any differences.…”
mentioning
confidence: 98%
“…Contact hypersensitivity (CHS) is a classic experimental model for the study of antigen-specific, T cell-mediated immune responses (1)(2)(3)(4). In CHS, typified by poison ivy dermatitis, initial sensitization occurs by topical application of an immunizing antigen, processing of antigen by skin dendritic cells (i.e., Langerhans cells), migration of antigen-bearing Langerhans cells to regional lymph nodes, and stimulation of naive T cells (5,6).…”
mentioning
confidence: 99%